Secretoneurin levels are higher in dilated cardiomyopathy than in ischaemic cardiomyopathy: preliminary results - Plášek, Jiří; Dodulík, Jozef; Lazárová, Marie; Stejskal, David; Švagera, Zdeněk; Chobolová, Nela; Šulc, Patrik; Evin, Lukáš; Purová, Dana; Václavík, Jan (Frontiers in Cardiovascular Medicine, 2024)
Background: Secretoneurin (SN) is a neuropeptide with potential utility as a biomarker of cardiovascular episodes. The main effect of SN is mediated through its inhibition of calmodulin-dependent kinase II (CaMKII), which influences calcium handling. We aimed to associate the levels of SN in plasma with different causes of heart failure. Methods: We prospectively enrolled consecutive patients with ischaemic (ICM) and dilated (DCM) cardiomyopathy from the outpatient heart failure clinic and healthy individuals. SN plasma levels were compared in DCM, ICM and healthy individuals with non-parametric tests. Results: A total of 53 patients (18.9% female; mean age 67.9± 12.6 years) and 34 healthy individuals (62% female) were included in the analysis. Plasma SN levels were significantly higher in the dilated cardiomyopathy (38.8 ± 27 pmol/L) as compared with the ischaemic cardiomyopathy (19.7 ± 22.6 pmol/L) group (P = 0.006). Plasma SN levels allowed DCM and ICM to be differentiated with 88% sensitivity and 61% specificity (P = 0.007), the cut of value is 13.3 pmol/L. Plasma SN levels differed significantly between healthy volunteers and both ICM (P0.0001) and DCM (P=0.049). Plasma SN levels did not differ according to age and were not associated with comorbidities, left ventricular ejection fraction, heart failure medication, troponin, creatinine, or natriuretic peptide plasma levels. Conclusion: Plasma secretoneurin levels differed significantly in DCM vs. ICM, being higher in the former. Based on plasma SN levels, discrimination between DCM and ICM might be possible. Healthy individuals produce higher SN plasma levels than stable HFrEF patients.